Tonkawa an Indian Language of Texas - Hoijer, Harry (Extract from Handbook of American Indian Languages, 1933)
Examines the history of the Tonkawa, a warlike tribe living in central Texas during most of the 18th and 19th centuries.  Focuses on the language spoken